The Effect of Meeting Rates on Matching Outcomes - Jaffe, Sonia; Weber, Simon (Economic Theory, 2019)
We extend the classic matching model of Choo and Siow (J Polit Econ 114(1):175–201, 2006) to allow for the possibility that the rate at which potential partners meet affects their probability of matching. We investigate the implications for the levels and supermodularity of the estimated match surplus.